Oxidative balance in brain after exposure to arsenic in ex vivo and in vivo models - Bonetto, Julián Gerardo (2017)
The hypothesis of this work was that radical generation after exposure to As may contribute to its toxic effects in the brain tissues. Oxidative status of brain was studied, both using ex vivo and in vivo protocols of exposure to the toxic. The generation rate of lipid radicals (LR●), and ascorbyl radical (A●) content, were measured by Electron Paramagnetic Resonance (EPR). In the ex vivo model control brain homogenates were exposed to As, and a 2-fold increase was detected in the LR● generation rate, with no changes in A● radical content. A significant decrease of 33% and 30% in the content of glutathione (GSH) was measured after exposure to 3.3 and 4.0 pmol As/mg FW, respectively. In the in vivo model, As was ip injected to rats and the rate of generation of LR● by homogenates of brain tissue, was increased by 81 and 122%, as compared to control animals after the injection of 3.0 and 5.8 mg As/kg, respectively. Neither GSH, nor -tocopherol (-T) nor ascorbate (AH-) content was affected in As-treated rats, as compared to the values from control animals. The LR●/α-T content ratio was significantly increased in As-treated animals as compared to control brains. The A●/AH− content ratio was not affected by As exposure. The content of total Fe showed non-significant differences between control and rat brains after 24 h of As administration. The data presented here showed new evidence on the generation of specific radical species by As treatment employing EPR methodologies in both, ex vivo and in vivo models. The data suggested the triggering of different pathways leading to some reactive species generation may occur accordingly to the via As reaches the brain, even when the same concentration of the toxic was achieved by the tissues.